The settlement of the Late Neolithic and Chalcolithic Travessa das Dores (Ajuda – Lisbon) - Neto, Nuno (2015)
In this article we present the results of the archaeological excavations at Travessa das Dores, Lisbon, that were performed before the construction of a new building for this location approved by the Lisbon city council. The excavations were limited to the area occupied by the new building. A significant number of pits were excavated during Late Neolithic in a cretaceous marly limestone platform. Soon after, an important defensive ditched enclosure was installed in the same place. Until now it is the first ditched enclosure excavated in Lisbon and North of Tagus River. The recollected artefacts typology from these two construction phases point out to a domestic occupation, with special emphasis to the abundant indented edges fragments, that points out to the same cultural phase. During the Chalcolithic this site knew had others less important domestic occupations; several fireplaces were identified in the ditch filling associated to Early and Full / Late Chalcolithic ceramics. Travessa das Dores settlement may be considered the most important prehistoric site identified and excavated in Lisbon city, according to the results we present now.